2018
DOI: 10.1038/s41416-018-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between tumour response and primary tumour location, and predictors of long-term survival, in patients with RAS wild-type metastatic colorectal cancer receiving first-line panitumumab therapy: retrospective analyses of the PRIME and PEAK clinical trials

Abstract: First-line panitumumab was associated with improved ETS and DpR vs. comparator in patients with left-sided mCRC. ETS may identify a subgroup of patients with right-sided disease who might respond to panitumumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
6
32
0
Order By: Relevance
“…Baseline patient demographics and disease characteristics by ETS status for the subgroup of patients who were symptomatic at baseline (29% [194/659]) are shown in Supplemental Table 3 in the online version. The existence of tumor-related symptoms at baseline was associated with a poorer prognosis; OS was reduced in these patients compared to patients with no symptoms at baseline (median [95% CI], 21 Figure 3B).…”
Section: Time To New Symptomatic Events By Ets and Dpr For Patients Wmentioning
confidence: 99%
See 3 more Smart Citations
“…Baseline patient demographics and disease characteristics by ETS status for the subgroup of patients who were symptomatic at baseline (29% [194/659]) are shown in Supplemental Table 3 in the online version. The existence of tumor-related symptoms at baseline was associated with a poorer prognosis; OS was reduced in these patients compared to patients with no symptoms at baseline (median [95% CI], 21 Figure 3B).…”
Section: Time To New Symptomatic Events By Ets and Dpr For Patients Wmentioning
confidence: 99%
“…Left-sided tumors are more common and are associated with a better prognosis and increased response to anti-EGFR treatment. [20][21][22] First-line panitumumab treatment has been associated with improved ETS and DpR compared to comparator treatments in patients with left-sided disease. 21 Further to this, existence of ETS !…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Several studies have shown more favourable tumour shrinkage with anti-EGFR therapy than with bevacizumab for right-sided tumours, suggesting that anti-EGFR antibodies could provide a means of achieving rapid control of tumour volume for certain classes of right-sided tumours. 45 Transcriptional biomarkers have also been studied in association with cetuximab efficacy (table 2). Upregulation of a specific microRNA, miR-31-3p, plays a significant role in activating RAS signalling and was identified as a potential negative predictor of cetuximab efficacy in the FIRE-3 study.…”
Section: Introductionmentioning
confidence: 99%